Aizuchi on Basic Japanese Language Textbook as Learning Material of Listening Behavior - Nishfullayli, Sa'idatun; Santiar, Lea (PAROLE: Journal of Linguistics and Education, 2023)
The low competence in listening behavior of Japanese language learners affects their interactional competence (Miyanaga, 2013). Textbooks, however, are not used optimally even though listening behavior teaching materials may greatly contribute to learner’s conversational skills, particularly for novice learners. This study examines the form and function of the Japanese listener response (aizuchi) by analyzing the structure of the dialogue model of the textbook ‘Minna no Nihongo I and Minna no Nihongo II.’ Using the interpersonal discourse system from Systemic Functional Linguistics, this study identifies aizuchi and non-aizuchi responses, mapping the distribution of aizuchi’s form and function in the textbook and describing variations in function and patterns of use of aizuchi-shi (short response). This study indicates two findings. Firstly, aizuchi is a listener’s response after the speaker’s statement (K1) and confirmation request (cf). Secondly, the short responses that have the highest frequency of use in the basic Japanese textbooks are referred to as aizuchi (aizuchi-shi): ‘soo desu ka,’ ‘soo desu ne,’ ‘ii desu ne,’ and ‘wakarimashita’; which has the function of understanding, supportive agreement, emotional/feeling expression, and turn-relinquishing. It concludes that basic Japanese textbooks are sufficient for teaching basic listening behavior because aizuchi is presented in various forms, functions, and usage contexts.